Projeto e análise de rectenas de baixa potência com simplificação e redução de circuitos casadores para reutilização de energia RF - Polyanna Mara Pereira (2019)
The reuse of energy available in the environment to feed low power devices has led to many different research. Within this context, this paper presents a theoretical and experimental study of a rectenna, which is an antenna coupled to a rectifier circuit. It is used in the capture and conversion of energy, available in the environment, in the range of microwave frequencies into electrical DC power. The use of rectennas to reuse electromagnetic energy is a recent application, which should take into account the characteristics of the received signal, such as high frequency and low power levels. These characteristics added to the non-linearity of the rectifier circuit imply limitations in the impedance matching between the antenna and the rectifier circuit, leading to the need for a specific design for each application. Generally the complete computational analysis of the rectenna system is complex as it is important to consider both parts: the antenna and rectifier circuit. Although the analysis of the electromagnetic problem coupled to the nonlinear circuit is possible, the simulation commonly has a high computational cost depending on the numerical method employed. Therefore, a retinal analysis tool consisting of a SPICE antenna circuit extraction model that allows the incorporation of the nonlinear circuit is presented as an alternative to full wave solutions based on numerical methods. The proposed methodology makes it possible to analyze the three-dimensional problem of the antenna and the rectifier circuit separately. Alternatively, two design methodologies based on antenna impedance optimization are proposed in order to increase the efficiency of the rectenna system. Firstly, a design technique based on antenna impedance optimization is proposed in order to reduce the complexity of the impedance matching circuit. Thus, the rectifier circuit is designed with a simple stub to keep the rectifier impedance close to 50Ω. The antenna impedance is optimized to match the measured rectifier. Then, the rectenna system designed with the impedance corrected antenna is compared to a system consisting of a 50Ω antenna for different distances. Finally, the results are validated based on experiments and data available in the literature. In order to completely eliminate the matching circuit, a second approach was developed where an antenna topology was optimized to allow direct matching with the rectifier circuit. The analysis of the voltage doubling rectifier circuit employed points to a relatively low impedance leading to the choice of a new antenna topology. The antenna tuning is presented and its results are compared with the initial technique and contemporary works presented in the literature.